The Ideopolitical Trends of Appropriating and AlteringArmenian Toponyms and Maps as Components of the “Greater Azerbaijan” Project - Stepanyan, Gevorg (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The political doctrine of Pan-Turkism proposed by Ziya Gökalp was intended to be implemented in a three-stage system. After the first stage, which involved the mass Turkification of the subject nations of the Ottoman Empire, the second stage was planned: the creation of an Oghuz state, which would include the Ottoman Empire, Eastern Transcaucasia, the Turkic-speaking countries of Central Asia (Khorezm), and the Iranian province of Atropatene-Azerbaijan. Within the scope of implementing the Oghuz state plan, a military-political concept was developed, consisting of both short-term and long-term strategies. Accordingly, the immediate plan envisaged, along with the conquest of Eastern Transcaucasia, the creation of a so-called “Azerbaijan” – an “East Caucasian Muslim” formation, which, as a temporary implementation phase, would become the main operational and political stronghold of the Young Turk-Musavat alliance. Subsequently, on the basis of this formation within the Ottoman Empire, a socalled “Great Azerbaijan” state was to be created, extending from the Black Sea to the Caspian Sea, from Batumi to Baku, including the Iranian Atropatene- Azerbaijan province. The long-term plan envisioned “Great Azerbaijan” as the first link in the creation of a pan-Oghuz state, which would bridge the Ottoman Empire with the Turkic-speaking peoples of Central Asia, ultimately laying the groundwork for the third phase –the establishment of a Turanian Empire under a common Pan-Turkic roof. Although the “Great Azerbaijan” project has periodically changed its tactics, its political goal has remained unchanged. During the Soviet era, realizing the impossibility of militarily annexing the Armenian territories, Azerbaijani leadership adopted a new strategy. Instead of massacres, persecutions, and forced displacements, they implemented a policy of ethnic cleansing, disenfranchisement, national discrimination, distortion of demographic data, Turkification of place names, cartographic falsifications, and appropriation of civilizational values. Մեծ Ադրբեջան» ծրագրի մարտավարության բաղադրիչ մասն է կազմում նաև Արևելյան Այսրկովկասի և բռնազավթված ի բնե հայկական տարածքների հայակերտ տեղանունների թյուրքացումը, տեղագրական ու պատմական քարտեզների կեղծումը, գործընթաց, որ տակավին սկսվել էր արհեստածին «Ադրբեջան» կազմավորման ժամանակներից: Հայկական տեղանունների միտումնավոր խեղաթյուրումը, դրանց ամեն կերպ թյուրքական հնչողություն տալը նպատակ ունի «ապացուցելու» զավթված տարածքների թյուրք-ադրբեջանական պատկանելության առասպելի «իսկությունը»: Այս նենգամիտ քաղաքականության հետևանքով հայկական տեղանունները, ենթարկվելով թուրքերենի արտասանական առանձնահատկություններին, կրեցին համապատասխան փոփոխություններ, որ ռազմավարական և ժողովրդագրական տեսակետից Հայաստանի համար հղի է լուրջ վտանգ-ներով:
Keywords: History